Business Model Innovation as a Mediator in Enhancing Entrepreneurial Success: A Study on Thai Herbal Entrepreneurs - Sermdamrongsa, Chawanvit (International Journal of Development Administration Research, 2025)
This study explores the factors influencing the success of Thai herbal entrepreneurs, with a specific focus on the mediating role of business model innovation. Using a quantitative research design, data were collected from 300 entrepreneurs and analyzed through structural equation modeling (SEM). The findings reveal that marketing innovation, access to financial resources, and government support have a significant impact on entrepreneurial performance, both directly and indirectly, through business model innovation. Notably, business model innovation serves as a critical mediating factor, highlighting the importance of adopting innovative business strategies to sustain competitive advantage. The study contributes to the literature by offering insights into how entrepreneurial success in resource-constrained industries can be achieved through continuous innovation. Theoretical and practical implications are discussed, with a particular emphasis on the role of policymakers and financial institutions in fostering an innovation-driven entrepreneurial ecosystem. Future research directions include exploring other mediators, such as technological adoption or organizational learning, and examining the generalizability of these findings in other sectors.